Impact of eating disorders on quality of life of women during the perimenopausal period - Ostrzyżek, Artur (Menopause Review/Przegląd Menopauzalny, 2013)
Eating disorders pose a serious medical, clinical and social problem. In the recent years cases of the lack of appetite are more often diagnosed in reference to middle-aged and elderly women. A situation like this may result from an existing disease process, a continuation of experiencing such problems in the past, and also a reflection of the trends being created by the modern media advocating the need for keeping a woman’s physical attractiveness in her late adulthood. It happens more and more often that the effort to reduce weight achieve a slimmer look is taken by women in their 50s, and even 60s. There is also an existing view that eating disorders among elderly women appear in a close connection to psychical disorders. Many women perceive menopause as a loss and a sign of an oncoming old age, thus they are focused mainly on negative emotions in this period of life. On the basis of depression-like disorders, there appear problems with controlling and maintaining the body mass. Although the scale of the phenomenon has still a limited range and character, its significant impact on life quality of women's population in the menopausal period justifies the execution of the current review of the subject literature in this matter.